2017
DOI: 10.1101/132134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling of biomechanics and biorheology of red blood cells in type-2 diabetes mellitus

Abstract: Erythrocytes in patients with type-2 diabetes mellitus (T2DM) are associated with reduced cell deformability and elevated blood viscosity, which contribute to impaired blood flow and other pathophysiological aspects of diabetesrelated vascular complications. In this study, by using a two-component red blood cell (RBC) model and systematic parameter variation, we perform detailed computational simulations to probe the alteration of the biomechanical, rheological and dynamic behavior of T2DM RBCs in response to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…For example, retinal vascular endothelial cells may have impaired ability to liberate endothelial nitric oxide synthase, thus affecting retinal vascular autoregulation. In addition, enhanced plasma viscosity, increased platelet aggregation, and decreased red blood cell deformability also lead to retinal and ONH perfusion problems . Fundamental structural alterations of capillaries in diabetes including endothelium dysfunction, vascular basement membrane thickening, pericyte apoptosis and capillary occlusion also involve small blood vessels in the ONH …”
Section: Discussionmentioning
confidence: 99%
“…For example, retinal vascular endothelial cells may have impaired ability to liberate endothelial nitric oxide synthase, thus affecting retinal vascular autoregulation. In addition, enhanced plasma viscosity, increased platelet aggregation, and decreased red blood cell deformability also lead to retinal and ONH perfusion problems . Fundamental structural alterations of capillaries in diabetes including endothelium dysfunction, vascular basement membrane thickening, pericyte apoptosis and capillary occlusion also involve small blood vessels in the ONH …”
Section: Discussionmentioning
confidence: 99%
“…We found that, in agreement with the experiments, margination of micro-beads increases with size and shear rate. We have introduced and validated a T2DM RBC model in our previous work (47). Here, we adopted the same red cell model for modeling the diabetic blood, whereas a T2DM platelet model is built based on the parameters informed by the clinical blood analysis of 64 diabetic patients.…”
Section: Resultsmentioning
confidence: 99%
“…Although the alteration in the size and shape of diabetic RBCs is still debatable and probably dependent on glycemic control of the study subjects, we considered extreme values for S/V that reported by Jin et al (56). We have recently proposed a T2DM RBC model (47), which has been validated with available experimental data. Following our previous study, here, we extend our T2DM RBC model (DRBC) to a suspension with cell properties similar to those of a NRBC except for a shear modulus, µ s = 2µ 0 (µ 0 is the shear modulus of healthy subjects), and a reduced S/V ratio, S/V = 1.04.…”
Section: Parameter Estimation Rbc Modelsmentioning
confidence: 97%